Comparison of the amount of artifacts induced by zirconium and titanium implants in cone-beam computed tomography images - Abbas Shokri; Fariborz Vafaee; Leila Haghighat; Shiva Shahabi; Maryam Farhadian; Mohammad Reza Jamalpour (BMC Medical Imaging, 2022)
Abstract Background This study aimed to compare the amount of artifacts induced by the titanium and zirconium implants on cone-beam computed tomography (CBCT) and assess the effect of different exposure settings on the image quality for both materials. Methods In this experimental study, 30 zirconium and 30 titanium implants were placed in bovine rib bone blocks. CBCT images were taken in two different fields of view (FOV: 4 × 6 cm2 and 6 × 8 cm2) and at two resolutions (133 µ and 200 µ voxel size). Subsequently, two observers assessed the images and detected the amount of artifacts around the implants through gray values. Data were analyzed by paired t test and independent t test using SPSS 21 and the 0.05 significance level. Results The results showed that titanium implants caused lower amounts of artifacts than zirconium implants, which was statistically significant (P < 0.001). The larger FOV (6 × 8 cm2) resulted in a lower amount of artifacts in both groups, although the results were only statistically significant in the zirconium group (P < 0.001). The amount of artifacts was increased when using the 133 µ voxel size in both groups, which was only significant in the zirconium group (P < 0.001). Conclusion Our results suggest that zirconium implants induce higher amounts of artifacts than titanium ones. We also concluded that the artifacts could be minimized using the larger FOV and voxel size.